Interest, concerns and strategies of LDCs in the Doha Round - Rahman, Mustafizur (Commonwealth Secretariat LondonGB, 2009)
Focuses on three issues of key interest to the LDCs in the context of the progress made in the negotiations as of December 2008. Examines development in key negotiating areas from the perspectives of LDCs. Puts the spotlight on some of the intra-LDC tensions that are emerging with regard to priority, perception and strategies being pursued.